Interoceptive experiences and ecological care: an embodied approach within therapeutical realms - González-Grandón, Ximena; Cadena-Alvear, Itzel; Gastelum-Vargas, Melina (Frontiers in Psychology, 2024)
The conventional dichotomy between human health and disease has historically been approached through reductionist models that emphasize the exclusive causal relevance of physiological and pathological processes. Consequently, self-awareness and affective dimensions, integral to a phenomenological perspective, are often relegated to secondary traits, affording little consideration for the causal role of embodied living organization. Our interest lies in exploring the potential relevance of the phenomenology of embodied self-awareness in relation to interoceptive processes within therapeutic settings. As we illustrate, when the unfolding processes of interoceptive awareness and its affective capacity take precedence, the agent assumes an active, rather than passive, role in their own experience of health or illness. Departing from an enactive, phenomenological, and ecological standpoint, we propose a distinctive perspective on interoceptive processes, relying on an affective conceptualization of a spectrum of experiences of bodily being-in-the-world. Our primary argument posits that considering interoceptive processes from an embodied and ecological viewpoint of the self, interacting with the material and social environment, enables an approach to the gradient of affective experiences of embodied self-awareness-where pleasure or suffering is perceived and felt-in a naturalized, non-reductive, and relational manner. We discern two ways in which interoceptive processes interrelate with the experience of embodied self-awareness: sensitivity (self-affective) and affective-laden perception. Drawing on this distinction, we provide a nuanced description of these experiences within communities of cis-women, exemplified through the contexts of menstruation and endometriosis. This exploration seeks to enhance our understanding of the phenomenology of embodied, ecological, and affective self-experience from within diverse and situated bodies. The goal is to contribute to their autonomy and ability to adapt and self-regulate within therapeutic contexts.